The Poggendorff illusion with nonparallel lines - Martišius, V. (Psichologija, 1995)
The paper studies the effect of some spatial parameters in the Poggendorff figure for illusion size. It was concluded that illusory distortions depend from the order of angles formed by the intersection of the transversal segments and nonparallel lines. When the first angle is smaller, the extent of illusion is greater. The distance from first transversal portion to remove end point of the first nonparallel line also effects the magnitude of illusion. The modern theories ignore such information and therefore they are not adequate.